'All the Laws in the Book': The Transgressive Impulse of Hammett's The Maltese Falcon. (March 2021) - Carlson, Matthew Paul
Abstract : Scholars of detective fiction have long acknowledged Dashiell Hammett's crucial role in the formation of the American hard-boiled style. However, a closer look at his third novel, The Maltese Falcon (1930), reveals the extent to which Hammett self-consciously engaged with the generic conventions of the Golden Age mysteries that had dominated the previous decade. By partially following the rules, Hammett continually toys with the reader's expectations, charting a new course for detective fiction while simultaneously offering a self-reflexive commentary on the genre's history. In addition to providing a fresh reading of The Maltese Falcon, this essay contextualises Hammett's efforts by showing how he responds to contemporary crime novelists, especially the American Willard Huntington Wright (better known by his pseudonym S. S. Van Dine). In 1928, Wright published his famous 'Twenty Rules for Writing Detective Stories' in an attempt to define the genre's specific appeal, creating a pact between author and audience. The Maltese Falcon explores the nature of that pact and ultimately violates it through a series of reversed expectations. By showing just how deeply embedded this transgressive impulse is in The Maltese Falcon, this essay sheds new light on a pivotal moment in both Hammett's career and in the evolution of detective fiction.